The Influence of Teaching Style and Independence on Learning Outcomes of Lower Passing in Volleyball Games for MAN Students - Herman Herman; Agung Sunarno; Nurhayati Simatupang (Journal Physical Education, Health and Recreation, 2021)
The learning process consists of several supporting components: teaching materials, learning models, learning methods, and teaching styles. All of these components aim to help students understand and understand all teaching materials in each subject. For the SMA/MA level, passing down in volleyball is one of the materials that is considered quite difficult, as evidenced by the data obtained from the school. More than half of the participants failed in the subject of the volleyball game. What is found in the field is the most significant cause of failure, which is generally influenced by an unsupportive learning process. One of the most influential things is the teaching style. In this study, the teaching styles that are considered to be able to create situations/conditions that help the learning process are convergent teaching styles and inclusive teaching styles.